2023
DOI: 10.1039/d2nh00573e
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal behavior of preferred formation of the cationic vacancies from the interior in a γ-GeSe monolayer with the stereo-chemical antibonding lone-pair state

Abstract: Two-dimensional (2D) materials tend to have the preferably formation of vacancies at the outer surface. Here, contrary to the normal notion, we reveal a type of vacancy that thermodynamically initiates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Therefore, the introduction of Ge vacancy provides a way for the stabilization of in γ-GeSe. We note that a recently published paper performed a similar analysis and confirmed that Ge vacancy formation can reduce the antibonding state in γ-GeSe …”
supporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the introduction of Ge vacancy provides a way for the stabilization of in γ-GeSe. We note that a recently published paper performed a similar analysis and confirmed that Ge vacancy formation can reduce the antibonding state in γ-GeSe …”
supporting
confidence: 93%
“…We note that a recently published paper performed a similar analysis and confirmed that Ge vacancy formation can reduce the antibonding state in γ-GeSe. 46 Next, we discuss the effect of SOC on γ-GeSe, as revealed by magnetoresistance (MR). The MR results showed a typical quadratic dependence on the magnetic field at all temperatures, as shown in Figure 5a.…”
mentioning
confidence: 99%
“…[ 44 ] Authors demonstrated that 1) V Ge showed the most stable defects regardless of Ge contents, 2) V Ge defects were formed spontaneously due to negative formation energies resulting in the Fermi level shifted below VBM, and 3) V Se were occupied with the defect states and hybridized with VBM. Very recently, Ke et al [ 45 ] revealed that the low formation energy for V Ge defect migration was originated to the antibonding coupling of the lone‐pair Ge 4 s and Se 4 p states near VBM. The V Ge defect played a role of shallow acceptor level leading to strong infrared light absorption and middle cationic Ge sublattice located V Ge defects were well passivated by Se layer, leading to long‐term stability for optoelectronic devices.…”
Section: Fundamental Properties and Theoretical Studies Of Gesementioning
confidence: 99%
“…Interestingly, bulk γ-GeSe was measured to have a higher electronic conductivity than that of graphite, rendering great possibilities in battery and thermoelectric applications. Many studies have been conducted to explore the unique structure on transport properties, , thermal conductivity, , high-performance thermoelectric, , ferroelectric, magnetic properties, photocatalytic activity, defect formation, strain-engineering behaviors, , and heterostructures. …”
Section: Introductionmentioning
confidence: 99%